Šel do světa na zkušenou - Hrdlička, Milan (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
In Czech, so called noun (substantive) adjectives belong to substantives. Concerning their forms, they are declined as adjectives, relating to one of the noun genders. Some of these noun adjectives are similar to real adjectives question – they can occur in all grammatical cases in communication. The other noun adjectives lost their adjective features. Some of these former adjectives, especially those feminine ones, occur in different adverbial meanings and are connected with a particular grammatical case only.
Keywords: noun; adjective; gender; declension